THE PEDAGOGUE'S MOBILITY AS THE WAY OF REALIZATION CONDITIONS OF THE NEW PEDAGOGICAL CONCEPT OF EDUCATION - Diachok, Nadiia (Educological discourse, 2019)
The article deals with professional mobility (the ability for successfully switching another activity or change the type of work) as a necessary quality of a modern pedagogical worker. It is highlighted the main qualities, which are important in the process of forming a professional mobile specialist. The result of the formed qualities is the creation of a professional style in accordance with the views of specialists, personal principles and orientations; constant search for optimal educational forms of learning, the implementation of a pedagogical experiment, production and generalization of experience in educational activities. The proposed criteria for evaluating pedagogical activity of educational workers according to the standards put forward by the society (professional self-development, professional skills, introduction of innovative technologies into the educational process, creativity in the period of reformation and modernization, the latest pedagogical technologies of activity). It is outlined the importance of the employees' professional mobility formation in accordance with the tasks of the new Concept of Pedagogical Education Development: the formation of universal skills of activity ensuring mobility as a personality; orientation to innovation activity; provision of fundamental social and humanitarian training as a mastering of professions of another profile; provision of wide professional training as a basis for possible mastering of other professions; strengthening of managerial training of future pedagogical staff; The result of the educational staff professional mobility formation is a sharp increase in the quality of training of all future teachers. The presence in society of a sufficiently large number of active, professionally mobile teachers becomes a guarantee of increasing its sustainability.